Pengaruh Model Pembelajaran Make A Match Berbasis Kartu Bergambar terhadap Hasil Belajar Siswa - Ragil Aria Irawan; Henry Aditia Rigianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Writing this study aims to determine the effect of the make a match learning model on student learning outcomes on heat transfer material for grade 5 SD Ki Ageng Giring. This research was conducted using a quantitative method with a pre-experimental design. The type of design chosen in this study is the One Group Pretest-Posttest Design. The sample used was grade 5 as many as 21 students as research subjects. Based on the data obtained, the results showed that there was an influence of the picture card-based learning model on student learning outcomes. This is supported by research data which shows a significance value of 0.00. Thus, based on the sig testing criteria <0.05, it can be concluded that Ha is accepted and Ho is rejected so that there’s a positive influence with the application of picture card-based make a match learning model on the learning outcomes of cognitive aspects of students in learning IPA heat transfer materials. This research is expected to be useful for all parties involved.